Mapping of Blast Disease Resistance Genes in BC2F6 Population of the Cross KDML105 × IR64 - Waiyalert, Aussanee; Sreewongchai, Tanee; Chaisan , Tanapon; Sripichitt, Prapa (Agriculture and Natural Resources, 2015)
The IR64 rice variety has a broad spectrum resistance to the blast pathogen in Thailand. Polygenic resistance genes have been identified in this variety. To detect quantitative trait loci (QTLs) controlling blast disease resistance, 192 BC2F6 lines (backcross inbred lines; BILs) derived from a cross between IR64 and KDML105 were used for gene mapping. The BILs were examined for the location of resistance genes using six virulent blast isolates. The presence was discovered of broad spectrum resistance loci in the IR64 variety positioned on chromosomes 2, 3, 8 and 12. Interestingly, two loci located on chromosomes 3 and 8 were new QTLs for blast disease resistance. These loci could be exploited in rice breeding programs for the development of broad spectrum and/or durable blast resistant rice varieties after being validated. According to the results of this study, the IR64 variety could be utilized as a donor parent of blast resistance loci to develop durable blast resistant varieties.